The application of in vivo reflectance confocal microscopy in dermatology - Kurzeja, Marta; Walecka, Irena; Rudnicka, Lidia; Olszewska, Małgorzata (Dermatology Review/Przegląd Dermatologiczny, 2010)
In vivo reflectance confocal microscopy is a novel non-invasive technique that allows real-time visualization of epidermis and superficial dermis with near histological resolution and good contrast. The method is most widely used in differential diagnosis of atypical or very early melanomas and other neoplastic skin diseases. Current literature indicates the possibility of widening indications for this diagnostic method. These include Darier’s disease, psoriasis, contact dermatitis, pemphigus and discoid lupus erythematosus. However, to date there are no studies assessing the sensitivity and specificity of in vivo reflectance confocal microscopy in these non-neoplastic diseases.